2019
DOI: 10.1002/isd2.12113
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the adoption of ICT for diabetes self‐management in South Africa

Abstract: The increasing disease burden in developing countries inhibits the provision of quality care to citizens. However, the increased availability of information communication and technology (ICT) tools makes this a viable option for inclusion in primary health care. Even so, barriers are impeding the successful adoption and usage of ICT tools in health care contexts. This research focuses on one such context to identify the challenges and barriers for the adoption of ICT tools for diabetes self‐management in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…This study also used the UTAUT model [16]. The research found that behavioural intention did not translate into usage [17]. This was due to the fact that almost 70% of respondents did not use forms of ICT, such as m-health applications, for their diabetes self-management.…”
Section: Challenges For User Acceptancementioning
confidence: 99%
See 3 more Smart Citations
“…This study also used the UTAUT model [16]. The research found that behavioural intention did not translate into usage [17]. This was due to the fact that almost 70% of respondents did not use forms of ICT, such as m-health applications, for their diabetes self-management.…”
Section: Challenges For User Acceptancementioning
confidence: 99%
“…Based on the areas identified by the study above [17], the objective of this study is to determine barriers for the acceptance of diabetes m-health applications, given the currently low levels of m-health use for diabetes self-management in the Western Cape.…”
Section: Challenges For User Acceptancementioning
confidence: 99%
See 2 more Smart Citations
“…This research provides new moderation variables in the South African context. Additionally, it was used in a study conducted in the Western Cape on the usage of ICT for diabetes self-management [29]. In that study, it was found that despite a high behavioural intention, there is low usage to almost 70% of the target population not using forms of ICT, such as mobile health.…”
Section: Introductionmentioning
confidence: 99%